The association of maternal gestational hyperglycemia with breastfeeding duration and markers of milk production. Issue 3 (8th May 2021) - Pang, Wei Wei; Geddes, Donna T; Lai, Ching-Tat; Chan, Shiao-Yng; Chan, Yiong Huak; Cheong, Clara Y; Fok, Doris; Chua, Mei Chien; Lim, Sok Bee; Huang, Jonathan; Pundir, Shikha; Tan, Kok Hian; et al.
ABSTRACT: Background: Previous studies focusing on the association between gestational diabetes and breastfeeding duration have been inconclusive. Objectives: We aimed to determine whether maternal gestational hyperglycemia is associated with the duration of breastfeeding and the concentrations of markers linked to breastmilk production. Methods: Data from the prospective, multiethnic Growing Up in Singapore Towards Healthy Outcomes study were used to assess the association of fasting plasma glucose (FPG) and 2-h postglucose challenge (2hPG) measured at 26–28 wk of gestation with duration of breastfeeding and concentrations of protein, lactose, citrate, sodium, potassium, and zinc in breastmilk 3 wk postpartum. Results: Of the 1035 participants, 5.2% and 9.5% had elevated FPG and 2hPG, respectively, consistent with a diagnosis of gestational diabetes mellitus based on International Association of Diabetes and Pregnancy Study Groups criteria. FPG ≥5.1 mmol/L was associated with a crude reduction in median breastfeeding duration of 2.3 mo. In a model adjusted for maternal prepregnancy BMI and intention to breastfeed, FPG ≥5.1 mmol/L predicted earlier termination of any breastfeeding (adjusted HR: 1.47; 95% CI: 1.04, 2.08) but not full breastfeeding (adjusted HR: 1.08; 0.76, 1.55). 2hPG ≥8.5 mmol/L was not significantly associated with the durations of any (adjusted HR: 0.86; 95% CI: 0.62, 1.19) or full (adjusted HR: 0.85; 95% CI: 0.62, 1.18) breastfeeding. Maternal FPG was significantly and positively associated with breastmilk sodium (adjusted coefficient: 1.28; 95% CI: 1.08, 1.51) and sodium-to-potassium ratio (adjusted coefficient: 1.29; 95% CI: 1.08, 1.54) but not with other measured breastmilk components. Conclusions: Women with FPG ≥5.1 mmol/L during pregnancy breastfeed for a shorter duration. Future work involving measurement of milk production is needed to determine whether low milk production predicts breastfeeding duration among women with elevated FPG. This trial was registered at www.clinicaltrials.gov as NCT01174875.